CHINA’S HIGH SPEED RAILWAY AND THE STRATEGIC INTEREST IN SOUTHEAST ASIA - Ahmad Mubarak Munir (Department of International Relations, University of Mataram, 2021)
The objective of this research is to elaborate the strategic advance that will be gained by China both in economic and political sectors. China’s transforming as a new global power, entered in five main destinations for foreign investment, become the consumer of 20%-25% of the world’s iron, steel, aluminum and third consumer of world oil production. China's ability in operating high technology attracts the world to admit China’s role in world politics. High-speed railway (HSR) technology started to investigate in 2004 and entered the production process in 2008; HSR becomes strategic tool for China when it promotes to Southeast Asia. By initiating HSR, China will be able to control the mobility of China's products in the region; the catalyst of the China’s southwestern growth; improving trade and the industrial sector. Supporting one belt one road policy and transforming the bad image of China will be the strategic way in the political sector. The elaboration of the soft power concept by Joseph Nye, Joshua Kurlantzick, and the Chinese conception is the guideline in this study. Qualitative analysis in library research is the main method. Data is taken from books, journals, reports, and websites.